RUANG PUBLIK PENDIDIKAN SEBAGAI RELASI ETNIK DAN AGAMA - Adam Latuconsina (Jurnal Studi Islam, 2020)
When Arab traders traveled to the archipelago, followed by the Portuguese and Dutch in the 16th century and the presence of Arab traders brought religion. Islam. Conflicts in various places including in Maluku, which have an impact on the pattern of inter-religious and ethnic relations. This phenomenon has an impact on relations in the public sphere, especially in universities, so that a good education pattern is needed for the formation of community character. This research is a qualitative descriptive study. The purpose of this research is to analyze the role of public education spaces in establishing ethnic and religious relations. The type of research is field research where data collection is done through observation, interviews, and documentation techniques, then analyzed through the stages of data reduction, data display, data interpretation and conclusion drawing. Research result; 1. Educational institutions are effective public spaces for the creation of ethnic and religious relations. This is possible because there are at least three main elements that are always involved in interactions or reciprocal relationships in the education public sphere, namely educators, students and parents. Through the interaction and assimilation of various elements in the education public sphere, everyone knows each other and learns from the diversity they have, individuals are expected to be able to transform themselves to find self-perception in encounters with other groups outside themselves, so as to form better inter-religious and ethnic relations. 2. Strategic educational institutions are used as media to form the character of the community (students) because the essence of education is to humanize humans.